2018
DOI: 10.1016/j.jcma.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The Shipai cohort for cardiovascular metabolic risk factors and outcome study — Design and preliminary results

Abstract: Our preliminary results revealed a high MetS percentage among young and middle-aged adults in Taiwan, with central obesity being a particularly urgent prevention target. The research design and operational protocol of this cohort study may stimulate more research in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Furthermore, amounting evidence has demonstrated significant gender differences in the prevalence of MetS in the United States, Europe, and Taiwan [24][25][26], with predominant evidence showing higher MetS prevalence in men than in women [24,25]. In addition, studies have shown that men and women have different risk factors for MetS.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, amounting evidence has demonstrated significant gender differences in the prevalence of MetS in the United States, Europe, and Taiwan [24][25][26], with predominant evidence showing higher MetS prevalence in men than in women [24,25]. In addition, studies have shown that men and women have different risk factors for MetS.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of MetS is at its highest all over the world, with a prevalence of 37.1% in the United States [2], 16.0% in Africa, 21.3% in Asia and 10.5% in Europe [3]. A significant gender difference was also observed in MetS prevalence in several studies from countries such as the US and Europe [4,5]. A recent study in China showed the prevalence of MetS as 33.3% for all participants (46.3% in males and 23.3% in females) [6].…”
Section: Introductionmentioning
confidence: 99%